Plausible biochemical mechanisms of chemotherapy-induced cognitive impairment (“chemobrain”), a condition that significantly impairs the quality of life of many cancer survivors - Ren, Xiaojia; Boriero, Diana; Chaiswing, Luksana; Bondada, Subbarao; St. Clair, Daret K.; Butterfield, D. Allan (Biochimica et biophysica acta. Molecular basis of disease, 2019)
Increasing numbers of cancer patients survive and live longer than five years after therapy, but very often side effects of cancer treatment arise at same time. One of the side effects, chemotherapy-induced cognitive impairment (CICI), also called “chemobrain” or “chemofog” by patients, brings enormous challenges to cancer survivors following successful chemotherapeutic treatment. Decreased abilities of learning, memory, attention, executive function and processing speed in cancer survivors with CICI, are some of the challenges that greatly impair survivors' quality of life. The molecular mechanisms of CICI involve very complicated processes, which have been the subject of investigation over the past decades. Many mechanistic candidates have been studied including disruption of the blood-brain barrier (BBB), DNA damage, telomere shortening, oxidative stress and associated inflammatory response, gene polymorphism of neural repair, altered neurotransmission, and hormone changes. Oxidative stress is considered as a vital mechanism, since over 50% of FDA-approved anti-cancer drugs can generate reactive oxygen species (ROS) or reactive nitrogen species (RNS), which lead to neuronal death. In this review paper, we discuss these important candidate mechanisms, in particular oxidative stress and the cytokine, TNF-alpha and their potential roles in CICI. [Display omitted] •CICI causes a significant decreased quality of life for cancer survivors.•Many ROS-associated chemotherapeutic agents do not cross BBB, yet brain is affected.•Brain oxidative stress, cytokines, mitochondrial dysfunction, apoptosis occur in CICI.•More research to better understand and potentially prevent CICI is needed.